Diagnostic and Management Challenges of Systemic Lupus Erythematosus in Pregnancy Complicated with Severe Preeclampsia and Intrauterine Growth Restriction: A Case Report - Suhartono, Azza Nurlaila; Giantari, Ifrinda; Setiaji, Danang; Putri, Rizky Ramadhani; Wajiih, Wildan Chanieful (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease more common in women than men. The risk of lupus flare increases during pregnancy. This case report describes the diagnostic and management challenges of SLE in pregnancy.Case Illustration: This case report describes a 27-year-old female, G3P1A1, 27 weeks of pregnancy, who presented with a six-hour history of headache, epigastric pain, and irregular uterine contractions. The patient has a poor obstetric history, with a miscarriage in her first pregnancy and an intrauterine fetal death (IUFD) in her second pregnancy. Ultrasonography showed an estimated fetal weight (EFW) of 878 grams. The laboratory test results revealed elevated levels with ANA of 140.2 units, anti-dsDNA of 1094 IU/mL, positive direct and indirect Coombs tests, and 1000 mg/dL urine protein. Conclusion: The diagnosis of SLE is established when a group of symptoms and signs are found according to the SLE Risk Probability Index criteria or the criteria for SLE in The Assessment using the European League Against Rheumatism/American College of Rheumatology. Early diagnosis of SLE in women is expected to prevent its impact on pregnancy. Management of SLE during pregnancy includes the use of hydroxychloroquine, azathioprine, steroid therapy, and addressing any complications that have occurred.Tantangan Diagnosis dan Tatalaksana Lupus Eritematosus Sistemik pada Kehamilan yang Disertai Preeklampsia Berat dan Restriksi Pertumbuhan Intrauterin: Sebuah Laporan KasusAbstrakPendahuluan: Systemic lupus erythematosus (SLE) adalah penyakit autoimun sistemik kronis yang lebih sering terjadi pada perempuan dibandingkan dengan laki-laki. Risiko lupus flare meningkat selama kehamilan. Laporan kasus ini bertujuan untuk menjelaskan tantangan diagnostik dan tatalaksana SLE pada kehamilan. Laporan Kasus: Laporan kasus ini menggambarkan seorang perempuan berusia 27 tahun, G3P1A1, usia kehamilan 27 minggu yang datang dengan keluhan nyeri kepala, nyeri epigastrium, dan kontraksi rahim tidak teratur selama enam jam. Pasien memiliki riwayat obstetri yang kurang baik, dengan keguguran pada kehamilan pertama dan kematian janin dalam kandungan (IUFD) pada kehamilan kedua. Pemeriksaan ultrasonografi menunjukkan estimasi berat janin (EFW) sebesar 878 gram. Hasil pemeriksaan laboratorium menunjukkan peningkatan ANA sebesar 140,2 unit, Anti-dsDNA sebesar 1094 IU/mL, tes Coombs langsung dan tidak langsung yang positif, serta protein urin sebesar 1000 mg/dL. Kesimpulan: Diagnosis SLE ditegakkan apabila ditemukan kumpulan gejala dan tanda sesuai SLE Risk Probability Index (SLERPI) atau kriteria SLE pada The assessment using the European League Against Rheumatism/American College of Rheumatology (EULAR/ACR). Penegakan dini SLE pada perempuan diharapkan dapat mencegah dampaknya pada kehamilan. Tatalaksana SLE selama kehamilan meliputi pemberian hydroxychloroquine, azathioprine, terapi steroid, serta penanganan komplikasi yang telah terjadi.Kata kunci: kehamilan, preeeklamsia, sistemik lupus eritematosus